Corporeal theology: the nature of theological understanding in light of embodied cognition - Tan, T (2017)
Appropriating insights from empirical findings and theoretical constructs of ‘embodied cognition,’ this study explores how theological understanding is accommodated to the bodily nature of human cognition. An emerging paradigm in cognitive science, embodied cognition proposes that human cognition depends upon bodily sensorimotor systems to ground concepts and to exploit environmental resources. A theological framework for exploring the human capacities which embodied cognition describes is the principle of accommodation, because it posits that revelation is accommodated to human capacities. Embodied cognition’s hypothesis that human concepts are grounded in sensorimotor states poses a theological quandary for God-concepts, since identifying God with sensorimotor content risks idolatry. The incarnation resolves this problem in theological epistemology by grounding God-concepts in bodily understanding, while avoiding idolatry. Thus, the incarnation represents an accommodation to human conceptual capacities. Embodied cognition further hypothesises that cognition relies on sensorimotor engagement with the world rather than internal mental representations. Subsequently, in addition to the brain, bodily states and environmental artefacts ‘scaffold’ cognitive processes. A scaffolded view of cognition highlights the cognitive import of embodied religious practices, which choregraph the body and curate material culture. I apply dozens of studies identifying mechanisms by which bodily or environmental factors influence cognition to the embodied and material dimensions Christian practices. On account of their inherent cognitive effects, practices are theorised to have intrinsic ‘embodied’ meanings alongside ‘symbolic’ ones established by conventions. Consequently, liturgy is seen as a bearer of theological content rather than merely an expression of it; a locus of religious experience; and a crucial determinate of religious and ethical formation. Again, the embodied nature of Christian liturgy is understood in terms of accommodation. Embodied cognition research helpfully illuminates the details of human embodiment to which theological understanding must be accommodated.